Marketing plans : how to prepare them, how to use them - McDonald, Malcolm. (Wiley, 2011)
"Marketing Plans, Seventh Edition presents a practical, no-nonsense style and approach that helps and encourages practicing managers with the difficult task of marketing planning. This helpful text illustrates the process of preparing a marketing plan, how to manage that process, and how to put the plan in action. The new edition has been thoroughly updated with contemporary thinking and includes new information on multi-channel integration and other new electronic routes to market. All case material and examples have also been revised."--